Photoluminescence upconversion at GaAs/InGaP2 interfaces driven by a sequential two-photon absorption mechanism - Hylton,N; Hinrichsen,TF; Vaquero-Stainer,AR; Yoshida,M; Pusch,A; Hopkinson,M; Hess,O; Phillips,CC; Ekins-Daukes,NJ (Physical Review B, 2016)
This paper reports on the results of an investigation into the nature of photoluminescence upconversion at GaAs/InGaP2 interfaces. Using a dual-beam excitation experiment, we demonstrate that the upconversion in our sample proceeds via a sequential two-photon optical absorption mechanism. Measurements of photoluminescence and upconversion photoluminescence revealed evidence of the spatial localization of carriers in the InGaP2 material, arising from partial ordering of the InGaP2. We also observed the excitation of a two-dimensional electron gas at the GaAs/InGaP2 heterojunction that manifests as a high-energy shoulder in the GaAs photoluminescence spectrum. Furthermore, the results of upconversion photoluminescence excitation spectroscopy demonstrate that the photon energy onset of upconversion luminescence coincides with the energy of the two-dimensional electron gas at the GaAs/InGaP2 interface, suggesting that charge accumulation at the interface can play a crucial role in the upconversion process.